Rational design of a deuterium-containing M2-S31N channel blocker UAWJ280 with in vivo antiviral efficacy against both oseltamivir sensitive and -resistant influenza A viruses. Issue 1 (1st January 2021) - Cáceres, C. Joaquín; Hu, Yanmei; Cárdenas-García, Stivalis; Wu, Xiangmeng; Tan, Haozhou; Carnaccini, Silvia; Gay, L. Claire; Geiger, Ginger; Ma, Chunlong; Zhang, Qing-Yu; Rajao, Daniela; Perez, Daniel R.; et al.
ABSTRACT: Seasonal influenza A virus (IAV) infections are among the most important global health problems. FDA-approved antiviral therapies against IAV include neuraminidase inhibitors, M2 inhibitors, and polymerase inhibitor baloxavir. Resistance against adamantanes (amantadine and rimantadine) is widespread as virtually all IAV strains currently circulating in the human population are resistant to adamantanes through the acquisition of the S31N mutation. The neuraminidase inhibitor-resistant strains also contain the M2-S31N mutant, suggesting M2-S31N is a high-profile antiviral drug target. Here we report the development of a novel deuterium-containing M2-S31N inhibitor UAWJ280. UAWJ280 had broad-spectrum antiviral activity against both oseltamivir sensitive and -resistant influenza A strains and had a synergistic antiviral effect in combination with oseltamivir in cell culture. In vivo pharmacokinetic (PK) studies demonstrated that UAWJ280 had favourable PK properties. The in vivo mouse model study showed that UAWJ280 was effective alone or in combination with oseltamivir in improving clinical signs and survival after lethal challenge with an oseltamivir sensitive IAV H1N1 strain. Furthermore, UAWJ280 was also able to ameliorate clinical signs and increase survival when mice were challenged with an oseltamivir-resistant IAV H1N1 strain. In conclusion, we show for the first time that the M2-S31N channel blocker UAWJ280 has in vivo antiviral efficacy in mice that are infected with either oseltamivir sensitive or -resistant IAVs, and it has a synergistic antiviral effect with oseltamivir.